180k views
1 vote
Which statement describes how to solve ^3 squareroot x^2-6= ^3 square root 2x+2

User Thugsb
by
6.0k points

2 Answers

3 votes

Answer:

Cube both sides and then solve the resulting quadratic equation.

Explanation:

It's the answer on edge

User Kacperito
by
5.5k points
3 votes

Answer:

Square both sides and then solves the resulting quadratic equations

Explanation:

The equation is 3sqrt(x^2-6)=3sqrt(2x+2)

We can solve this by;

First square both sides;

(3√(x²-6))²= (3√(2x+2))²

We obtain;

9(x²-6)=9(2x+2)

We simplify to obtain a quadratic equation;

x²-6=2x+2

= x²-2x-8=0

Then we solve the quadratic equation;

x²-4x+2x-8=0

x(x-4)+2(x-8)=0

(x+2)(x-8)=0

Values of x = -2 or 8

User Innokenty
by
5.0k points